Preparation and evaluation a new formula of denture cleansers (a comparative study) - Taqa, Amer A.; Y. K. Bashi, Tarik; M. Al –Aubadi, Safwan (International Journal of Dental Research, 2016)
The objective of this study is to prepare and study chemical compounds for cleaning denture from locally available materials. The chemical compounds solutions were (sodium bicarbonate with alum), (sodium bicarbonate with citric acid), (sodium bicarbonate with apple vinegar), (sodium bicarbonate with clear commercial vinegar), (sodium bicarbonate with thyme oil), (saturated salt solution), (clear commercial vinegar), (alum). The main study, the effects of the chemical compounds solutions were evaluated on the (color, water Sorption and transverse strength) of heat cured denture base material. The t-test showed that the highest increase in optical density for the specimens immersed in (alum), (sodium bicarbonate +alum), (sodium bicarbonate + apple vinegar) solutions at 1/2 hr immersion and it increased more at 8 hrs immersion. The conclusions of this study showed that the safest prepared solutions on the denture base material that could be used as denture cleansers are (sodium bicarbonate7gwith clear commercial vinegar5ml), (sodium bicarbonate 2g with thyme oil 3.57g), (saturated salt solution 40g) at 1/2 hr and 8 hrs of immersion. While, (sodium bicarbonate 2g with citric acid 4.57g) solution appeared its safety at 1/2 hr immersion only.